Evaluating Financial Performance in Jordan’s Insurance Sector: A CARMEL Model Analysis - Shihab, Ruba Nimer Abu; Khaliq, Shatha Yousef Abdul; Shihab, Abdulrahman Nimer Abu; Abdelazeem, Mohamed Ahmed Lotfy; Algebaly, Esam Aldin M. (Journal of Posthumanism, 2025)
The main objective of the study is evaluation the financial performance of five selected operating Insurance Companies in Jordan(Jordan Insurance (JOIN), Middle East Insurance (MEIN), Al-Nisr Al-Arabi Insurance(AAIN), Gulf Insurance Group - Jordan(GIG), Solidarity First Insurance (FINS)) through the use of CARMEL model indicators by using the analytic descriptive method in collecting and analyzing data for the financial statements of the Jordan insurance sector During The period 2015– 2018. The study reveals strong capital adequacy across all firms, with ratios exceeding benchmarks, underscoring their resilience to financial shocks. However, moderate asset quality signals long-term risks if asset performance deteriorates. Reinsurance practices exhibited volatility, with retention ratios fluctuating between 34% and 84%, reflecting inconsistent risk-sharing strategies. While most firms maintained stable liquidity, AAIN faced recurrent cash shortages, highlighting liquidity management gaps.Management soundness metrics underscored workforce inefficiencies, emphasizing the need for enhanced training to improve operational effectiveness. Profitability analysis yielded mixed results: AAIN and FINS demonstrated consistent returns (ROE/ROA), whereas JOIN and GIG experienced sharp declines, with GIG’s ROA plunging to -10.46% in 2017 due to significant losses.The findings reveal a sector with foundational stability but critical vulnerabilities. To strengthen long-term competitiveness, the study recommends prioritizing asset quality optimization, workforce upskilling, strategic reinsurance alignment, and rigorous liquidity oversight. These measures aim to mitigate risks, enhance profitability, and align Jordan’s insurance sector with global best practices. This research provides actionable insights for regulators and industry leaders to foster sustainable growth in a dynamic economic landscape.